1996
DOI: 10.1002/j.1460-2075.1996.tb00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Rho-associated kinase, a novel serine/threonine kinase, as a putative target for small GTP binding protein Rho.

Abstract: The small GTP binding protein Rho is implicated in cytoskeletal responses to extracellular signals such as lysophosphatidic acid to form stress fibers and focal contacts. Here we have purified a Rho‐interacting protein with a molecular mass of approximately 164 kDa (p164) from bovine brain. This protein bound to GTPgammaS (a non‐hydrolyzable GTP analog).RhoA but not to GDP.RhoA or GTPgammaS.RhoA with a mutation in the effector domain (RhoAA37).p164 had a kinase activity which was specifically stimulated by GTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
761
2
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 976 publications
(783 citation statements)
references
References 54 publications
17
761
2
3
Order By: Relevance
“…Bombesin (10 nM; panel c) and ET-1 (10 nM; panel e) stimulated actin stress fiber formation in PC-3 cells. The Rho-associated coiled-coil forming protein kinases p160ROCK/ROCK-1 (Ishizaki et al, 1996 and ROCK-a/ROCK-2 (Leung et al, 1996;Matsui et al, 1996) are direct downstream effectors of RhoA that regulate actin stress fiber formation. They are specifically inhibited by the synthetic pyridine derivative, Y-27632 (Uehata et al, 1997;Ishizaki et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Bombesin (10 nM; panel c) and ET-1 (10 nM; panel e) stimulated actin stress fiber formation in PC-3 cells. The Rho-associated coiled-coil forming protein kinases p160ROCK/ROCK-1 (Ishizaki et al, 1996 and ROCK-a/ROCK-2 (Leung et al, 1996;Matsui et al, 1996) are direct downstream effectors of RhoA that regulate actin stress fiber formation. They are specifically inhibited by the synthetic pyridine derivative, Y-27632 (Uehata et al, 1997;Ishizaki et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…ROCK may also be present in related intracellular compartments and be involved in Rho-mediated cytoskeletal regulation. Recently, Leung et al [20] and Matsui et al [21] identified rat and bovine protein kinases as putative Rho targets, which are homologous to human p160 ROCK. The sequences of these protein kinases show much higher homology with mouse ROCK-II than mouse ROCK-I, although the reported rat sequence does not contain the segment corresponding to the amino-terminal region of ROCK-II.…”
Section: O Nakagawa Et Al/febs Letters 392 (1996) 189-193mentioning
confidence: 99%
“…Among the known downstream effectors of Rho proteins, Rho kinases might be potential candidates for mediating RhoB-F effect on centrosome overduplication and mitotic cell death. Rho kinases have been localized at the cell membrane, 29 at the cleavage furrow in late mitosis, 30 and, more recently, for p160ROCK in centrosomes. 31 Furthermore, p160ROCK is required for centrosomal positioning and centrosome-dependent exit from mitosis.…”
Section: Rhob-f Inhibits Radiation-induced Mitotic Cell Death and Cenmentioning
confidence: 99%